Predictive capacity of indicators of adiposity in the metabolic syndrome in elderly individuals - Bacelar Duarte de MORAIS, Keila; Oliveira MARTINHO, Karina; Silva FRANCO, Fernanda; PESSOA, Milene Cristine; Queiroz RIBEIRO, Andréia (Revista de Nutrição, 2023)
Objective To evaluate the predictive ability of adiposity indicators as MetS predictors in elderly individuals. Methods Cross-sectional study enrolled in the Estratégia Saúde da Família (Family Health Strategy). Anthropometric measurements were measured. Body Mass Index, Waist-Hip Ratio, Waist-Height Ratio, Conicity Index and Body Adiposity Index were calculated. Blood was collected and resting blood pressure was measured. MetS was classified according to the harmonizing criteria. The predictive ability of anthropometric variables was evaluated using Receiver Operating Characteristic curves. Results Regarding male individuals, our research indicates that the BMI, Waist-Height Ratio and Waist Hip Ratio are better predictors and they are equivalent to each other. As for female individuals, results show that the Body Mass Index and Waist-Height Ratio are better predictors and equivalent to each other. Conclusion Waist-Height Ratio and Body Mass Index are good MetS predictors for elderly individuals, especially among men. More research in this area is important. Comitê de Ética em Pesquisa com Seres Humanos da Universidade Federal de Viçosa. (Viçosa University Ethics Committee in Research with Human Beings) (nº 039/2011).